Evaluation of Innovation Efficiency of Listed Baijiu Enterprises Based on Three-stage DEA Model - Li, Xiyao; Chen, Yijun (International Journal of Global Economics and Management, 2024)
Baijiu industry, as a pillar industry of hundreds of billions of dollars, is an important part of the national economy, and has been strongly supported by the national and local governments at all levels. However, as China's consumption upgrading speeds up, the process of the liquor industry is accelerating, and the market competition led by homogenised products is intensifying, liquor enterprises need to seek an innovation path suitable for their own enterprises in order to form a sustainable competitive advantage. Using a three-stage DEA model, this paper measures the innovation efficiency of 18 listed liquor enterprises in 2022, and analyses the relationship between environmental variables and the innovation efficiency of listed liquor enterprises. The results show that environmental factors such as government subsidies, GDP per capita, and equity concentration all have a significant impact on the slack variables of the firms' R&D expenditure investment and the slack variables of R&D personnel investment. From a general point of view, the innovation efficiency of China's listed liquor enterprises still needs to be improved, and the gap between enterprises is large.